Cross-Cultural Psychology: The Concept of Sadness In The Perspective of Javanese Culture - Sulaiman, Tryo Pandu; Shofiah, Vivik; Rajab, Khairunnas (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In Islam, bullying has been experienced by the prophet Yusuf a.s who was abused by his brother and then thrown into a well. However, along with the development of technology, bullying is also carried out through social media or what is commonly known as Cyberbullying. This action is also bullying but is carried out with the help of technology such as social media with the aim of hurting someone’s feelings through an online message. So cyberbullying is an indirect violence aimed at damaging someone’s mentality to future conditions. This research was conducted using the literature study method. This method is also called Library research. This study aims to examine the procedures and interventions of Bullying and Cyberbullying from an Islamic perspective. Cyberbulling is an action carried out with the help of technology such as telephones or social media, which aims to hurt and oppress someone. Cyberbulling actions are carried out intentionally or not and will cause a traumatic impression on the victim. Cyberbulling subjects are called Bullies and Cyberbulling victims are also called Victims. Slightly different from Bullying, Cyberbullying can be done by a group of people in different areas, this is done with social media to disturb the comfort of the victim.